2016
DOI: 10.1073/pnas.1525444113
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Protein L4 is essential for Epstein–Barr Virus Nuclear Antigen 1 function

Abstract: Epstein-Barr Virus (EBV) Nuclear Antigen 1 (EBNA1)-mediated origin of plasmid replication (oriP) DNA episome maintenance is essential for EBV-mediated tumorigenesis. We have now found that EBNA1 binds to Ribosome Protein L4 (RPL4). RPL4 shRNA knockdown decreased EBNA1 activation of an oriP luciferase reporter, EBNA1 DNA binding in lymphoblastoid cell lines, and EBV genome number per lymphoblastoid cell line. EBV infection increased RPL4 expression and redistributed RPL4 to cell nuclei. RPL4 and Nucleolin (NCL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“… 13 EBNA1 is an EBV-encoded nuclear antigen which plays a critical role in EBV genome maintenance, replication and postmitotic segregation and is the only EBV protein expressed in all types of EBV-infected cells. 4 We have previously demonstrated that EBV-EBNA1 promotes the production of Treg cells in a TGFβ1-dependent manner. 14 However, the role and specific mechanism of EBV-EBNA1 in chemoattraction of Treg cells remains poorly understood.…”
Section: Discussionmentioning
confidence: 97%
“… 13 EBNA1 is an EBV-encoded nuclear antigen which plays a critical role in EBV genome maintenance, replication and postmitotic segregation and is the only EBV protein expressed in all types of EBV-infected cells. 4 We have previously demonstrated that EBV-EBNA1 promotes the production of Treg cells in a TGFβ1-dependent manner. 14 However, the role and specific mechanism of EBV-EBNA1 in chemoattraction of Treg cells remains poorly understood.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, many RPs exhibit dramatically higher levels of expression in cells where virus propagate rapidly, such as RPL4 in EBV-infected cells [94] and RPS27a in Hepatitis B virus-infected cells [137]. These RPs with high expression can be considered as targets of antiviral drug carriers for specific tissue/cell drug delivery.…”
Section: Applications and Prospectivementioning
confidence: 99%
“…The ChIP assay was performed to detect the binding of EBNA1-oriP according to previous reports (Shen et al, 2016). The Immunoprecipitation Kit (Millipore) was used for the assay.…”
Section: Chromatin Immunoprecipitation (Chip) Assaymentioning
confidence: 99%
“…EBNA1-oriP binding has been validated to be necessary for the replication initiation of EBV genome (Shen et al, 2016). Here, we investigated the effect of CYPA knockdown on the oriP luciferase activity in cells transfected with an oriP luciferase reporter in C2089 cells.…”
Section: Cypa Regulates Transcription Initiation Of the Ebv Genome VImentioning
confidence: 99%